2022
DOI: 10.1038/s41598-022-10587-0
|View full text |Cite
|
Sign up to set email alerts
|

High serum concentrations of growth differentiation factor-15 and their association with Crohn’s disease and a low skeletal muscle index

Abstract: Sarcopenia comprises a low skeletal muscle index (SMI) and low muscle strength (MS) or low physical function. Many sarcopenia biomarkers have been reported. With Crohn’s disease (CD), a low SMI is predictive of intestinal complications. Therefore, many CD studies have reported that sarcopenia is defined by SMI alone. This study investigated the sarcopenia frequency by assessing the SMI and MS of Japanese patients with CD and biomarkers predicting a low SMI. We evaluated the SMI using a bioelectrical impedance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Target same receptors as myostatin [163] Limited number of studies [163] Unknown Muscle protein turnover GDF-15 Increased Correlate with muscle mass and performance tests [42][43][44] Limited number of studies [163] Increased with renal insufficiency [49] Muscle protein turnover Not modified by exercise in long-term interventional studies [32,35] Irisin Decreased Associated with muscle mass and strength [56,164] No interventional studies [80] Unknown…”
Section: Unknownmentioning
confidence: 99%
See 1 more Smart Citation
“…Target same receptors as myostatin [163] Limited number of studies [163] Unknown Muscle protein turnover GDF-15 Increased Correlate with muscle mass and performance tests [42][43][44] Limited number of studies [163] Increased with renal insufficiency [49] Muscle protein turnover Not modified by exercise in long-term interventional studies [32,35] Irisin Decreased Associated with muscle mass and strength [56,164] No interventional studies [80] Unknown…”
Section: Unknownmentioning
confidence: 99%
“…Several cohorts have shown increased GDF-15 expression in sarcopenic participants [40,41]. GDF-15 was also sometimes, but not systematically, associated with handgrip strength, skeletal muscle index (SMI) [42][43][44] and physical performance tests [45,46]. Myostatin and follistatin expression is induced upon acute physical exercise [47].…”
Section: Muscle Collagen Turnovermentioning
confidence: 99%
“…GDF-15 has recently gained recognition as a key age-associated cytokine, with elevated serum concentrations positively correlated with all-cause mortality (46, 47), multimorbidity (48), frailty (49,50) and sarcopenia (51)(52)(53), while recent work by Kim-Muller et al demonstrated that GDF-15 neutralisation restored both muscle mass and function in mice (54). In line with these data and consistent with other reports in CLD (55, 56), we observed signi cantly greater circulating levels of GDF-15 in CLD patients, which were positively associated with muscle epigenetic age acceleration, further supporting an aged phenotype of the skeletal muscle in CLD patients.…”
Section: Discussionmentioning
confidence: 99%
“…As GDF15 is a myokine, its circulating levels are negatively correlated with muscle mass in numerous diseases, including COPD, intensive care unit-acquired weakness (ICUAW), Crohn's disease, pulmonary hypertension (PH) and CC (30,(55)(56)(57)(58). Muscle atrophy, including that of skeletal, chest, diaphragm and cardiac muscle, is a hallmark of CC and a major cause of mortality in patients with cancer (4,59).…”
Section: Gdf15 and Muscle Atrophy In CCmentioning
confidence: 99%